2021
DOI: 10.1029/2020ef001620
|View full text |Cite
|
Sign up to set email alerts
|

Climatic Drivers of Extreme Sea Level Events Along the Coastline of Western Australia

Abstract: Extreme sea level (ESL) events are a primary driver of coastal flooding along most coastlines worldwide

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…It is likely that these turbidity drivers (higher water levels, wave power and rainfall) along with cyclones (due to the immense, but short-lived, wave power and winds) are the mechanism behind increased turbidity in the Gulf during La Niña phases of ENSO. We found many of these drivers (waves, rainfall, higher water levels) were intensified in the Exmouth Gulf region during the La Niña phase of ENSO (Figure 5) and this has been shown by others [45,77,93]. Furthermore, cyclonic activity is increased during La Niña phases in north Western Australia [94] and strong turbidity peaks are known to be associated with these events [47].…”
Section: Body Of Gulfsupporting
confidence: 70%
See 1 more Smart Citation
“…It is likely that these turbidity drivers (higher water levels, wave power and rainfall) along with cyclones (due to the immense, but short-lived, wave power and winds) are the mechanism behind increased turbidity in the Gulf during La Niña phases of ENSO. We found many of these drivers (waves, rainfall, higher water levels) were intensified in the Exmouth Gulf region during the La Niña phase of ENSO (Figure 5) and this has been shown by others [45,77,93]. Furthermore, cyclonic activity is increased during La Niña phases in north Western Australia [94] and strong turbidity peaks are known to be associated with these events [47].…”
Section: Body Of Gulfsupporting
confidence: 70%
“…The strongest driver of turbidity along this coastline was the La Niña phase of ENSO (highest at the 10-month lag). It is known that this phase is also associated with increased sea level anomalies throughout the region as well as increased cyclonic and wave activity [74][75][76][77]. The positive phase of the Indian Ocean Dipole (pIOD) was also significantly correlated with turbidity along the inshore eastern coastline of the Gulf.…”
Section: East Coastmentioning
confidence: 99%
“…We show that tidal variability is the key determinant in locational variations of still water level extremes, even in locations where coastal flooding is presently exclusively surge‐driven. In other words, the highest tides coincide with the period of lowest atmospheric pressure, most frequent strong cold fronts, and hence, highest monthly mean sea levels (Lowe et al., 2021). This likely arises from tidal analyses including monthly and seasonal variations in mean sea level due to climatic variability in wind and pressure patterns.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Indeed, extreme water levels are often due to the combination of atmospheric conditions (strong winds, low atmospheric pressure), of high waves, and of high tides. It should be noted, however, that lower frequency sea level variability, such as that due to oceanic general circulations (including mesoscale activity, seasonal to interannual and decadal variability) can also contribute to extreme water levels (e.g., Melet et al, 2016;Fernandez-Montblanc et al, 2020;Lowe et al, 2021). Non-linear effects and retroactions between wave, ocean and atmosphere can alter the simulation of extreme events.…”
Section: Evolutions Of Total Water Forecastsmentioning
confidence: 99%
“…For instance, without such structures large parts of the Netherlands would be permanently submerged or threatened by flood events as about a third of the Netherlands is located below sea level. Recently, Lowe et al (2021) found that considering a sea level rise ranging from 0.3 to 2.0 m by 2100, it is economically efficient to protect 13% of the global coastline (which encompasses 90% of the global flood plain population). In Europe, elevating dykes in an economically efficient way along the 24-32% of the coastline would allow to avoid at least 83% of flood damages, with a benefit to cost ratio of such an investment ranging from 7 to 15 depending on climate change and socio-economic scenarios (Vousdoukas et al, 2020b).…”
Section: Exposure Mapping Coastal Defense Structuresmentioning
confidence: 99%